2016
DOI: 10.1016/j.expneurol.2015.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the monocyte chemokine CCL2 in dorsal root ganglion neurons causes a conditioning-like increase in neurite outgrowth and does so via a STAT3 dependent mechanism

Abstract: Neuroinflammation plays a critical role in the regeneration of peripheral nerves following axotomy. An injury to the sciatic nerve leads to significant macrophage accumulation in the L5 DRG, an effect not seen when the dorsal root is injured. We recently demonstrated that this accumulation around axotomized cell bodies is necessary for a peripheral conditioning lesion response to occur. Here we asked whether overexpression of the monocyte chemokine CCL2 specifically in DRG neurons of uninjured mice is sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 87 publications
(134 reference statements)
5
77
2
Order By: Relevance
“…The concept that manipulating the immune response may be beneficial for remyelination is not new (Pavelko et al, ). Past studies report both beneficial and detrimental outcomes (Triarhou and Herndon, ) and current studies link polarization of macrophages to an M2 phenotype as being beneficial to both CNS and PNS repair (Kigerl et al, ; Mokarram et al, ; Niemi et al, ; Wang et al, ; Ydens et al, ). However, our study is first to show that brief increases in neuronal activity can drive the polarization of immune cells toward an M2 pro‐repair phenotype, coincident with faster and more robust remyelination (M c Lean et al, ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The concept that manipulating the immune response may be beneficial for remyelination is not new (Pavelko et al, ). Past studies report both beneficial and detrimental outcomes (Triarhou and Herndon, ) and current studies link polarization of macrophages to an M2 phenotype as being beneficial to both CNS and PNS repair (Kigerl et al, ; Mokarram et al, ; Niemi et al, ; Wang et al, ; Ydens et al, ). However, our study is first to show that brief increases in neuronal activity can drive the polarization of immune cells toward an M2 pro‐repair phenotype, coincident with faster and more robust remyelination (M c Lean et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…This is similar to the response we have observed in the 8 day focally demyelinated nerves subjected to ES 3 days previously, with higher levels of Schwann cell-expressed MCP1 being observed in conjunction with increased macrophage numbers and the majority of these macrophages polarized to an M2 phenotype. Increased CCL2 has also been shown to drive pro-regenerative responses in sensory neurons (Boivin et al, 2007;Kwon et al, 2015;Niemi et al, 2016), suggesting that the ability of ES to shift the balance in favor of the M2 phenotype in our focal demyelination model is likely key to our observed improvements in remyelination (M c Lean et al, 2014).…”
Section: Es Modulates Chemokine Signaling Andmentioning
confidence: 85%
See 1 more Smart Citation
“…PNS injury upregulates Ccl2 in DRGs [27,74,75] and FMNs [76]. So far, CCL2 has been attributed functions during nerve injury-associated immune responses mainly by regulating monocyte rather than neuronal responses [2329].…”
Section: Resultsmentioning
confidence: 99%
“…Although it is known that JAKs are activated via membrane glycoprotein 130 (gp130; also known as IL6Rβ) signalling 68 , it is unclear which ligands are responsible for gp130 activation and their source. Several studies have suggested that interleukin 6 (IL-6) 6971 and CC-chemokine ligand 2 (CCL2) produced by macrophages 72 are responsible for gp130 activation in DRG neurons, whereas astrocytic expression of ciliary neurotrophic factor (CNTF) 73 and leukaemia inhibitory factor (LIF) 74 activate gp130 in RGCs. pSTAT3 is retrogradely transported by the molecular motor dynein to the cell soma 57 .…”
Section: Injury Signallingmentioning
confidence: 99%